Flexural-tensegrity snapping tails for bio-inspired propulsion in fluids. (October 2022) - Boni, Claudio; Reis, Pedro M.; Royer-Carfagni, Gianni
Abstract: Many aquatic animals propel themselves by flapping their tails. Leveraging a recently proposed snapping cantilever beam based on the concept of flexural tensegrity, we propose a bio-inspired propulsion device. The design comprises a segmental beam with hollow voussoirs in unilateral contact along tailor-shaped surfaces, held together by a prestressed internal cable. Prescribing relative periodic rotation to a pair of consecutive control segments of the structured beam produces multi-articulated sequential snapping of all joints. We built a series of prototypes and performed precision experimental tests in water to characterize their propulsive capacity. A parametric study was carried out to characterize the dependence of the thrust produced by the oscillating tail on the following factors: number of segments, shape of the internal cavities dictating the cantilever curvature, and mobility constraint of a fin appended at the end of the tail. The results provide a proof of concept that our design for a snapping structured beam can be used as a propulsive device. We further demonstrate the feasibility of this propulsion unit to propel a toy boat in a water basin.